Cote d'Ivoire : 2013 Article IV Consultation and Fourth Review Under the Extended Credit Facility Arrangement. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that Cote d'Ivoire is recovering from a long period of economic stagnation and political conflict that culminated in the post-election crisis of end-2010 and early 2011. The conflict caused real per capita income to fall by more than 40 percent from its 1978 peak level. Following the post-election crisis, the new government started the process of sociopolitical normalization, and quickly put in place an economic recovery program. Growth is projected to reach 8.7 percent in 2013, while inflation is expected to remain below the regional convergence criterion of 3 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet